Health behaviours and depressive symptoms in higher education Portuguese students - Sabino, Bebiana (2023)
Introduction: The transition to higher education and the long duration of university studies have implications for students’ health behaviours. They are faced with greater autonomy of choice but also with greater academic obligations that condition their behaviour. The purpose of this study is to determine which health behaviours differentiate higher education students with moderate to severe depressive symptoms from those with mild to low symptoms. Material and methods: A cross-sectional study was conducted with 166 Portuguese higher education students (58.4% males). The health behaviours assessed were physical activity and sitting time through the International PA Questionnaire – Short Form (IPAQ-SF), active choices through the Active Choice Index Questionnaire, and sports practice and sleeping time through the National Dietary and Physical Activity Survey. Depressive symptoms were assessed using the Patient Health Questionnaire-9. The Mann-Whitney test was used to assess gender differences in depressive symptoms. An Odds-Ratio was calculated to establish the probability of being classified with moderate to severe depressive symptoms. Results: 24.1% of students showed moderate to severe depressive symptoms. In an analysis by gender, it was found that girls spend less time sitting on average than boys (p < 0.001). Students with moderate to severe depressive symptoms show on average more sitting time (p = 0.018) and less sleep time during weekdays (p = 0.005). Conclusions: Sitting time and sleep time are health behaviours that are associated with higher depressive symptoms in higher education students. Higher education institutions are considered to play a key role in promoting health behaviours that can interfere with students’ mental health.